BUSINESS COMPETENCES ESTIMATION AND DEVELOPMENT - Spica, Inese; Guzikova, Ludmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Taking into consideration at the present business environment of the Russia, as well as its geographical position and the historical background, it is important to make use of these conditions for estimation and further development business competences at the universities of Russia. The object of the present research paper is business competences, the subject of the research paper is estimation of the business competences of Russia and the development them in the study process at the higher education organizations in Russia. The objective of the research paper is to study the integration process of students and academic staff representing Russian higher education organizations in formation of business competences in Russia, to elucidate the factors influencing the business competences, to develop proposals for estimation and improvement of business competences in Russia. Research methods: reported analysis of business competences, higher education organizations in Russia, study of correlation between business environment factors and business competences, economic and statistical analysis of the universities results, economic experiment, studying of public and non -governmental institutions data in Russia. The present paper includes further development of study on the contents of business competences, factors influencing it, higher education theory and policy.